Gender Identity in a Second Language: The Use of First Person Pronouns by Male Learners of Japanese. Issue 2 (4th March 2017) - Brown, Lucien; Cheek, Elizabeth
ABSTRACT: This is a qualitative sociocultural study examining how five advanced-level learners of Japanese from the United States use gendered first person pronouns to negotiate their identities. Japanese does not have a ubiquitous pronoun such as English I . Instead, the language contains forms that are marked for formality and gender, including watashi (formal/feminine), ore (informal/masculine) and boku (neutral/boyish). We collected recordings of the learners speaking with four different native-speaker interlocutors (female friend, male friend, female stranger, male stranger) and conducted retrospective interviews. The analysis shows that these learners were actively involved in choosing pronouns that indexed their identities as men, although these masculine identities were not always ratified by their Japanese interlocutors. One reason for this was that the male identities expressed by the learners were at times closer to American than to Japanese masculinities. Learners also used pronouns as a resource to index their identities as proficient speakers of Japanese.